PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT BATHIN VIII KABUPATEN SAROLANGUN JAMBI - DAHMIRI, .; WAHYUNI, SRI (Jurnal Manajemen Terapan dan Keuangan, 2016)
Abstract This study entitledEffect of Education and Training Employee Performance Against Bathin At Head Office VIII. This study aimsto determine the effectof educationand trainingto employee performanceat thesub-district office Bathin VIII. The method used is quantitative research. Data obtained by spreading the question naire to the respondent by 39 peopleas samples. Further more, the data were processed using SPSS computer device 17, as well as regression analysis toprove the hypothesis of the study. The results showed that education and training contributes to the performance of employees at Head Office Bathin VIII with the coefficient of determination r squere of 0.399, which means 39.9% change inemployee performance variable (Y) can be explainedby the influence of Education and Training(X). Keywords: Educationand Training, Performance and Employee